Organization of Devices Information in Ontology Representation to Support Service Composition - Kelvin Choy Chuong, Wen; Wong Sau, Peng; Tan Su, Wei; Mohamad Zaini, Norliza (2008)
Nowadays, with rapid development in networking technology, inter-device communication and controlling has getting easier. Existing technologies such as UPnP, Jini and HAVi address the device communication issue. However, there is still lack of a mechanism for organizing device information into useful inputs for service composition. Thus, we propose an ontology-based schema to support dynamic service composition and selection of networked devices. In our proposal, networked devices are organized in ontologies based on: (i) device's functionality and (ii) device's profile (e.g. device's IP address, location and usage status). By referring to the ontologies, our system can determine the suitable devices that are capable to do certain task based on device's functionality. Ontology also provides a shared understanding of device information to achieve interoperability of devices on the network. Proper classification of device information has significantly assist user's decision in selecting appropriate device to perform desired service.